Development of a Science E-Module Based on Problem Based Learning Using Moodle to Improve Students' Science Literacy and Critical Thinking Abilities - Anas Sumarhadi; Supahar Supahar (Journal of World Science, 2025)
The purpose of this research is to produce a problem-based learning science e-module using Moodle that is (1) suitable for improving scientific literacy and critical thinking skills; (2) practical for teachers and students to use in enhancing scientific literacy and critical thinking skills; and (3) effective in improving students' scientific literacy and critical thinking abilities. This research employs Research and Development with the 4D development model (define, design, develop, and disseminate). The study was conducted at Abu Bakar Integrated Islamic Junior High School, Yogyakarta, during the 2024/2025 academic year. Prior to the research, the developed product and learning tools were tested for feasibility by two experts and for practicality by teachers and students in a limited trial. The results of the study indicate that the problem-based learning science e-module using Moodle to improve students' scientific literacy and critical thinking skills: (1) is feasible for use, based on very high content validity, empirical evidence of validity that fits the Rasch model (mean INFIT MSNQ value = 1), and reliability categorized as sufficient; (2) very practical to use, based on teacher assessments, and categorized as practical based on student readability responses; and (3) effective to use, as shown by a significant increase in students' scientific literacy and critical thinking skills according to MANOVA test results, with the effect size value of the treatment categorized as medium.